2010
DOI: 10.2478/s11772-010-1033-8
|View full text |Cite
|
Sign up to set email alerts
|

THz/sub-THz bolometer based on electron heating in a semiconductor waveguide

Abstract: Direct detection THz/sub-THz bolometer is proposed. In it an electromagnetic wave propagates in the bipolar semiconductor waveguide, heats electrons and holes there, and therefore creates their bipolar thermodiffusion flow and, as well as, the electromotive force (emf). The flow causes the carrier excess concentration. Both this concentration and emf are used to get the bolometer response voltage. The bolometer theoretical model is developed. The possibility without cooling or moderate cooling (about 100 K for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…At the low biases, the calculated NEP of investigated In-n-Hg 0.61 Cd 0.39 Te-In detectors , when there available are the thermal and shot noises. The presence of Schottky barriers does not affect strongly on the NEP value, as compared to the same structures that were investigated in the framework of hot-electron bolometer theory [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the low biases, the calculated NEP of investigated In-n-Hg 0.61 Cd 0.39 Te-In detectors , when there available are the thermal and shot noises. The presence of Schottky barriers does not affect strongly on the NEP value, as compared to the same structures that were investigated in the framework of hot-electron bolometer theory [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The structures of this type were investigated earlier in the framework of hot-electron bolometer theory [9], and it demonstrated sensitivity to radiation in ν = 0.037…1.54 THz frequency range at temperatures T ~70…300 K. However, during studying the electrical characteristics and sensitivity of these structures to radiation, we found that current-voltage characteristics of some samples deviate from linear behavior even at room temperature. In this case, their photoresponse as a function of the bias current does not match the behavior, predicted by the theory for hot-electron bolometer [9] and observed experimentally in Hg 1-x Cd x Te structures with ohmic contacts previously [10]. Some samples had linear current-voltage characteristics at room temperature, but at liquid nitrogen temperature these characteristics were significantly nonlinear.…”
Section: Sensitive Structures Based On Hg 1-x CD X Te and Their Electmentioning
confidence: 99%
“…In this paper, ground of the model is stated only and more de− tailed explanation can be found in Ref. 20. Here, the thin layer of bipolar semiconductor with the concentrations of shallow donors N d and acceptors N a , respectively, is a a sen− sitive element with the thickness a 1 , the width a 2 , and the distance a 3 between the metal contacts which serve as an− tennas.…”
Section: Modelmentioning
confidence: 99%
“…Under the influence of incident THz radiation, the changes in HEB (hot electron bolometer) sensitive element parameters take place at the length of several micrometers [6] and are much less compared to antenna dimensions, through which the radiation power is introduced to HEB. The antenna dimensions are conditioned by its effective area A eff = Gλ 2 /4π and are close to the wavelength λ, G is the antenna gain [7].…”
Section: Mct Detectors Architecture and Experimental Set-upmentioning
confidence: 99%
“…The use of un-cooled MCT detector as THz with other detection mechanism compared to IR region was offered in [6], where the properties of a free electron gas heated by THz radiation were analyzed. Thus, there is an opportunity varying the characteristics of sensitive layers to apply such MCT detector technology for simultaneous operation in different spectral regions, which makes these systems more informative.…”
Section: Introductionmentioning
confidence: 99%